Co, N-doped carbon sheets prepared by a facile method as high-efficiency oxygen reduction catalysts. Issue 52 (28th November 2022) - Zhang, Wei; Pei, Supeng; Xu, Kangwei; Han, Zhiyue; Ma, Jialu; Zhang, Yingge; Liu, Guipeng; Xu, Xiaojun
Abstract : The Co, N-doped carbon sheets as high-efficiency ORR catalysts were prepared by a facile process. Abstract : Transition metal and nitrogen codoped carbon materials have emerged as one of the most promising candidates to replace noble metal-based oxygen reduction reaction (ORR) catalysts. However, the development of high-efficiency, stable and low-cost metal–nitrogen–carbon catalysts still remains a challenge. In this study, cobalt and nitrogen codoped carbon sheet catalysts were successfully prepared by a simple self-injected vapor phase growth and template method. The catalysts exhibited a multilevel pore structure with a large specific surface area and resulting physical characteristics. The catalysts have excellent onset and half-wave potentials during the ORR. Notably, the onset ( E 0 ) and half-wave potential ( E 1/2 ) in alkaline media for the Co-N-C-43.8 catalyst are 31 mV and 3 mV higher than those of a commercial Pt/C catalyst, respectively. Moreover, the durability of the Co-N-C-43.8 catalyst remains at a 93% current density after 10 000 s, while that of a commercial Pt/C catalyst only remains at 83%. Also, the Co-N-C-43.8 catalyst has little change in the current density after the addition of methanol. These results indicate that the Co, N-doped carbon sheet is a promising ORR catalyst.